Biocidal Activity of N-Halamine Methylenebisacrylamide Grafted Cotton. Issue 2 (June 2015) - Li, Xiaolin; Liu, Ying; Liu, Yin; Du, Jinmei; Li, Rong; Ren, Xuehong; Huang, Tung-Shi
Methylenebisacrylamide (MBA) was coated on cotton fabric via free radical polymerization with the aid of initiator. The surface of grafted fabric was characterized by FTIR and SEM, which confirmed that MBA was grafted onto cotton cellulose via covalent bonding. Exposure to dilute sodium hypochlorite solution was found to render the grafted fabric biocidal. The chlorinated cotton was found to inactivate 99.97% of Staphylococcus aureus and 99.99% of Escherichia coli O157:H7 within 30 min of contact time, respectively. The washing stability and UV irradiation recharge ability of coated fabric were also investigated. After 24 h exposure to UV light, over 92% of chlorine was recovered upon chlorination.